KONSEP WATERFRONT KALI MBEROK KOTA LAMA SEMARANG - Fitriana, Mira (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2021)
Â Abstract: Kali Mberok Kota Lama Semarang is a river that has a lot of history during the Dutch colonial era in Central Java. The revitalization of the Kota Lama area is now being carried out by turning old buildings into places for office activities and also for supporting tourism activities in the Old City. The development of the revitalization of the Kota Lama cultural heritage area was hampered by the problem of tidal flooding and street lighting. The waterfront concept for Kali Mberok is one solution to overcome the obstacles to revitalizing the Old City by adding green open spaces on the edge of Kali Mberok. The implementation of a waterfront in Kali mberok Kota Lama will have a positive impact on reducing buildings on the riverbank and also increasing street lighting with the addition of public open spaces. Innovatively, this study will lead and develop the potential of Kali Mberok in the design of Kali Mberok waterfront tourism around Kota Lama with an emphasis on the Waterfront conceptAbstrak: Abstrak Kali Mberok Kota Lama Semarang adalah salah sungai yang memiliki banyak sejarah di masa kolonial Belanda di Jawa Tengah. Revitalisasi kawasan Kota Lama kini dilakukan dengan memfungsikan gedung gedung tua menjadi tempat kegiatan perkantoran dan juga tempat kegiatan penunjang pariwisata di Kota Lama.Â Perkembangan revitalisasi kawasan cagar budaya Kota Lama sempat terhambat karena adanya masalah banjir rob dan peneranganÂ jalan. Konsep waterfront untuk Kali Mberok menjadi salah satu solusi untuk mengatasi kendala revitalisasi Kota Lama dengan penambahan ruang terbuka hijau di pinggir Kali Mberok. Penerapan waterfront di Kali mberok Kota Lama akan memberikan dampak positif untuk mengurangi bangunan di pinggir sungai dan juga menambah penerangan jalan dengan penambahan ruang terbuka publik. Secara inovatif, kajian ini akan mengarah dan mengembangkan potensi yang dimiliki oleh Kali Mberok pada desain perancangan wisata tepian air Kali Mberok disekitar Kota Lama dengan penekanan konsep Waterfront.